DESAIN PEMBEKALAN ENTERPRENEURSHIP BAGI WARGA BINAAN PEMASYARAKATAN PADA FASE PRA ASIMILASI BERBASIS ASMAA-UL HUSNA - Pangestuti, Dinik Fitri Rahajeng (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
Prisons are places that have very negative connotations in society. People who have lived life in the majority prison get a slant in society. This condition leads to a decrease in self-concept so that former Warga Binaan Pemasyarakatan (WBP) will experience social constraints when returning to society after the punishment. Therefore it is necessary that there is a provision that can provide the spirit for the WBP to have an adequate lifeskill. The method of learning is already present in the Qur'an, which is "Recite by (name) the name of your Lord who created, He has created man from a clot of blood. Read, and your Lord is the Most High, who teaches men with pens. He taught man what he did not know. "(Q.S Al 'Alaq: 1-5). This verse is the first verse revealed to Rasululloh SAW, which is a sign that he is the one chosen to carry the apostolic duty, which is bringing a message of mercy to all of nature (rahmatan lil alamin). This study aims to explore, foster and develop the potential of Warga Binaan Pemasyarakatan (WBP) by providing treatment to raise self-awareness and positive personality by way of dhikr Asmaa-ul Husna. The research method used is a mixed methode research with approach of community based action research. The data collected in the form of quantitative and qualitative data. For quantitative data is processed by using Paired Sample T-Test, while the qualitative data will strengthen the test results quantitatively. This study shows that there is a significant change in the character of enterpreneurship, peace of mind and well being before and after the program.